HUBUNGAN PENGGUNAAN KONTRASEPSI HORMONAL DENGAN KEJADIAN HIPERTENSI PADA WANITA USIA REPRODUKTIF (15-49 TAHUN) DI WILAYAH KERJA PUSKESMAS TELADAN KOTA MEDAN TAHUN 2019 - manik, risda mariana (Jurnal Kesehatan Medika Udayana, 2020)
ABSTRACT Background: The government established a family planning (KB) program to regulate the population in Indonesia through the use of contraceptives. The most attractive contraception for women is hormonal contraception, which is 47.54% injections and 23.58% pills. The main concern with the use of hormonal contraceptive methods is an increased risk of hypertension. The use of contraceptives containing the hormones estrogen and progesterone can cause an increase in blood pressure. Based on the 2013 Riskesdas data, the prevalence of hypertension in Indonesia is 26.5%. The prevalence of hypertension in women tends to be higher than men which is 22.8% for men and 28.8% for women. Method: This research is an observational survey research, case-control design. Held in the Work Area of ??the Medan City Primary Health Center. Conducted from March-June 2019. The population in this study were all women of productive age (15-49 years) totaling 572 people. The size of the case sample was 35 people and 35 controls. Case samples were taken by means of consecutive sampling, control samples were taken by convenient sampling. Data analysis was performed univariately and bivariately using the Chi Square statistical test (?2) with a significance level of 0.05. Result: In the hypertension group, 77.1% used hormonal contraception and 22.9% did not use hormonal contraception. Whereas in the non hypertensive group 62.9% did not use hormonal contraception only 37.1% used hormonal contraception. There is a relationship between hormonal contraceptive use and hypertension in women of reproductive age. A value (OR = 5.7; 95% CI 2,008-16,244) means that women of reproductive age are at risk of experiencing hypertension 5.7 times greater if women of reproductive age use hormonal contraception than those who do not use hormonal contraception. Conclusion: Women of reproductive age are at risk of developing hypertension when using hormonal contraception. Therefore, it is recommended that women of reproductive age limit early use of hormonal contraception and prefer non-hormonal contraception or natural contraception. If using hormonal contraception to keep monitoring blood pressure regularly at least 3 months after using hormonal contraception and immediately stop using hormonal contraception if there is an increase in blood pressure. Keyword: Hormonal contraception, Hypertension, Women at Reproductive age